Executive summary of the 2021 SAEM consensus conference: From bedside to policy: Advancing social emergency medicine and population health through research, collaboration, and education. (15th March 2022) - Schoenfeld, Elizabeth M.; Lin, Michelle P.; Samuels‐Kalow, Margaret E.
Abstract: Background: Social emergency medicine (social EM) examines the intersection of emergency care and the social factors that influence health outcomes. In 2021, the SAEM consensus conference focused on social EM and population health, with the goal of prioritizing research topics, creating collaborations, and advancing the field of social EM. Methods: Organization of the conference began in 2019 within SAEM. Cochairs were identified and a planning committee created the framework for the conference. Leaders for subgroups were identified, and subgroups performed literature reviews and identified additional stakeholders within EM and community organizations. As a result of the COVID‐19 pandemic, the conference format was modified. Results: A total of 246 participants registered for the conference and participated in some capacity at three distinct online sessions. Research prioritization subgroups were as follows—group 1: ED screening and referral for social and access needs; group 2: structural competency; and group 3: race, racism, and antiracism. Thirty‐two "projects in progress" were presented within five domains—identity and health: people and places; health care systems; training and education; material needs; and individual and structural violence. Conclusions: Despite ongoing challenges posed by the COVID‐19 pandemic, the 2021 SAEM consensus conference brought together hundreds of stakeholders to define research priorities and create collaborations to push the field forward.